2006
DOI: 10.1038/ng1767
|View full text |Cite
|
Sign up to set email alerts
|

Common loss-of-function variants of the epidermal barrier protein filaggrin are a major predisposing factor for atopic dermatitis

Abstract: Atopic disease, including atopic dermatitis (eczema), allergy and asthma, has increased in frequency in recent decades and now affects approximately 20% of the population in the developed world. Twin and family studies have shown that predisposition to atopic disease is highly heritable. Although most genetic studies have focused on immunological mechanisms, a primary epithelial barrier defect has been anticipated. Filaggrin is a key protein that facilitates terminal differentiation of the epidermis and format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
2,239
15
92

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,615 publications
(2,406 citation statements)
references
References 25 publications
60
2,239
15
92
Order By: Relevance
“…AD patients are particularly susceptible to recurrent skin infections, especially with SA [51]. Altered skin barrier function may partially explain SA colonization in AD, and a high percentage of these patients have mutations in filagrin [52], an important structural protein. However, considering that skin barrier defects also exist in psoriasis patients, who are by comparison more resistant to skin infection, a different explanation for microbial susceptibility of the AD patients was necessary.…”
Section: Atopic Dermatitis and Infections Due To A Failure Of Host Inmentioning
confidence: 99%
“…AD patients are particularly susceptible to recurrent skin infections, especially with SA [51]. Altered skin barrier function may partially explain SA colonization in AD, and a high percentage of these patients have mutations in filagrin [52], an important structural protein. However, considering that skin barrier defects also exist in psoriasis patients, who are by comparison more resistant to skin infection, a different explanation for microbial susceptibility of the AD patients was necessary.…”
Section: Atopic Dermatitis and Infections Due To A Failure Of Host Inmentioning
confidence: 99%
“…The most important layer of the skin in maintaining this barrier function is the outer layer, the stratum corneum (Madison, 2003). How well the skin functions as a barrier varies between individuals and could be affected by a number of factors including the -E-mail: maeve.palmer@afbini.gov.uk thickness of the stratum corneum (Holbrook and Odland, 1974), the number of hair follicles in the skin (Wosicka and Cal, 2010) and genetic mutations (Palmer et al, 2008). There are links between skin permeability and occurrence of bacterial skin disease, for example, humans who suffer from an inflammatory skin condition called atopic dermatitis, which is associated with an impaired skin barrier function (Di Nardo et al, 1998), are more susceptible to some bacterial, viral and fungal infections of the skin (Jung and Stingl, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that two functional mutations in the gene encoding filaggrin (FLG) are strong risk factors for AD and asthma in European populations. 35 Other studies demonstrated that these mutations result in an extrinsic AD in patients suggesting that the skin barrier defect precedes the development of allergic sensitization in AD. 157 Since FLG mutations have not been commonly described in other non European populations, studies have analyzed mutations in other ancestral groups to determine the contribution of FLG mutations to AD pathogenesis worldwide.…”
Section: Epidermal Differentiation Complexmentioning
confidence: 99%
“…32 The region on chromosome 1q21 contains the epidermal differentiation complex (EDC) where a number of genes associated with epidermal differentiation and barrier function reside. 33,34 Recent reports have shown that two functional mutations in the epidermal differentiation complex gene filaggrin (FLG) are strongly associated with AD, the asthma often accompanying AD, 35 and also the common skin disorder ichthyosis vulgaris. 36 The FLG gene encodes for a protein profilaggrin, which becomes cleaved in the suprabasal keratinocytes to form the active protein filaggrin.…”
Section: Skin Barrier Dysfunctionmentioning
confidence: 99%